2016
DOI: 10.1111/dmcn.13364
|View full text |Cite
|
Sign up to set email alerts
|

Association between corpus callosum development on magnetic resonance imaging and diffusion tensor imaging, and neurodevelopmental outcome in neonates born very preterm

Abstract: In newborn infants born very preterm, brain injury is associated with changes in simple metrics of corpus callosum development. In this population, the development of the corpus callosum, as reflected by size and microstructure, is associated with neurodevelopmental outcomes at 18 months corrected age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 24 publications
6
40
3
Order By: Relevance
“…A positive association was observed with FA measures whereas a negative association was found with mean MD measures. This is consistent with recent findings where preterm infants with abnormal cognitive outcome at 18 months CA had significantly lower mean FA at CC compared to the preterm infants with normal outcome (Malavolti, Chau et al 2017). This result, that a higher mean FA at CC is associated with better cognitive outcome, is consistent with the significant positive associations between mean FA at CC and cognitive scores observed in this thesis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A positive association was observed with FA measures whereas a negative association was found with mean MD measures. This is consistent with recent findings where preterm infants with abnormal cognitive outcome at 18 months CA had significantly lower mean FA at CC compared to the preterm infants with normal outcome (Malavolti, Chau et al 2017). This result, that a higher mean FA at CC is associated with better cognitive outcome, is consistent with the significant positive associations between mean FA at CC and cognitive scores observed in this thesis.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that fibre organization and axonal density in CC are associated with cognitive function. In particular, lower FA in CC was observed in infants with abnormal cognitive outcomes when compared to infants with normal outcomes (van Kooij, de et al 2012, Malavolti, Chau et al 2017.…”
Section: Corpus Callosum (Cc)mentioning
confidence: 99%
“…Twenty‐six studies acquired early structural MRI data . Results of meta‐analyses are presented in Table and Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In a study of infants with periventricular leukomalacia, those who progressed to severe CP (Gross Motor Function Classification System [GMFCS] levels III–V) had smaller thalamic volumes than no or mild CP (GMFCS levels I–II) . A study investigating length and cross‐sectional area of the corpus callosum found no association of length, total area, anterior or middle third area of the corpus callosum with motor outcomes . A smaller area of the posterior third of the corpus callosum was associated with adverse motor outcomes …”
Section: Resultsmentioning
confidence: 99%
“…Malavolti et al suggest that simple corpus callosal MRI measurements in the neonatal period are of prognostic value for predicting motor and cognitive outcome in infants born preterm. In addition to providing metrics of size (regional area and length), they demonstrate a further advantage of MRI by identifying a significant relationship between a quantitative measure of white matter integrity (fractional anisotropy) and clinical outcome.…”
mentioning
confidence: 99%